Identification And Characterisation Of Coliphages From Seawater In Batu Ferringhi, Penang - Lai, Ching Wee (2018)
Pathogenic microorganisms in polluted recreational seawater would be harmful to beachgoers and marine lives. Coliphages are recognised as bioindicator for the presence of human viruses in water quality monitoring. Thus, the purpose of this study was to survey the phage diversity in the polluted seawater in Batu Ferringhi and to study the characteristics of the isolated phages. The morphology of five isolated phages was determined through transmission electron microscopy visualisation. Three isolated coliphages that infected E. coli ATCC 11303 were suggested belonged to Myoviridae, whereas two coliphages which specific to E. coli ATCC 13706 were of Microviridae.